CONCEPTUAL METAPHOR IN A COLLECTION OF ACEHNESE FOLK SONG LYRICS: A COGNITIVE SEMANTIC STUDY - Kartika, Rika; Mulyadi, Mulyadi (Universitas Islam Sumatera Utara (UISU), 2024)
This study aims to analyze the use of conceptual metaphors in a collection of Acehnese folk song lyrics using a cognitive semantic approach. Employing a qualitative method, the research focuses on cognitive semantic analysis to explore and understand the meanings embedded in Acehnese folk song lyrics with depth and precision. The sample collection involves selecting a diverse set of Acehnese folk song lyrics performed by Rafli Kande, including Aneuk Yatim, Wasiet Keu Aneuk, and Jasa Poma, which represent a variety of themes, genres, and time periods. The technique employed is text analysis, which examines song lyrics in depth to identify conceptual metaphors based on their types, such as ontological, structural, or orientational metaphors. The study identifies key metaphors in Acehnese folk songs, reflecting cultural values like familial bonds, social hierarchies, and spiritual beliefs. These metaphors illustrate the interconnectedness of nature and human life, emphasizing reverence for the environment and the cyclical nature of existence. Overall, Acehnese folk songs serve to preserve cultural heritage, reinforce collective identity, and provide moral guidance, showcasing their significance in Acehnese society.